Abnormal Chest Computed Tomography Findings among Admitted Symptomatic COVID-19 Patients in a Tertiary Care Centre: A Descriptive Cross-sectional Study - Sujit Pant; Bina Basnet; Sujata Panta; Neeraj Basanta Tulachan; Kalpana Rai; Mukunda Singh Shrestha (Journal of Nepal Medical Association, 2022)
Introduction: COVID-19 has emerged as a pandemic and has varied clinical presentation. Computed Tomography scans of the chest play an important role in evaluating the lung parenchymal changes and aids in better planning the management of COVID-19 patients. The purpose of this study was to find the prevalence of abnormal chest computed tomography findings among admitted symptomatic COVID-19 patients in a tertiary care centre.